Alzheimer’s Toxic Amyloid Beta Oligomers: Unwelcome Visitors to the Na/K ATPase alpha3 Docking Station - DiChiara, Thomas (Yale J Biol Med, 2017)
Toxic amyloid beta oligomers (AβOs) are known to accumulate in Alzheimer’s disease (AD) and in animal models of AD. Their structure is heterogeneous, and they are found in both intracellular and extracellular milieu. When given to CNS cultures or injected ICV into non-human primates and other non-transgenic animals, AβOs have been found to cause impaired synaptic plasticity, loss of memory function, tau hyperphosphorylation and tangle formation, synapse elimination, oxidative and ER stress, inflammatory microglial activation, and selective nerve cell death. Memory loss and pathology in transgenic models are prevented by AβO antibodies, while Aducanumab, an antibody that targets AβOs as well as fibrillar Aβ, has provided cognitive benefit to humans in early clinical trials. AβOs have now been investigated in more than 3000 studies and are widely thought to be the major toxic form of Aβ. Although much has been learned about the downstream mechanisms of AβO action, a major gap concerns the earliest steps: How do AβOs initially interact with surface membranes to generate neuron-damaging transmembrane events? Findings from Ohnishi et al (PNAS 2005) combined with new results presented here are consistent with the hypothesis that AβOs act as neurotoxins because they attach to particular membrane protein docks containing Na/K ATPase-α3, where they inhibit ATPase activity and pathologically restructure dock composition and topology in a manner leading to excessive Ca++ build-up. Better understanding of the mechanism that makes attachment of AβOs to vulnerable neurons a neurotoxic phenomenon should open the door to therapeutics and diagnostics targeting the first step of a complex pathway that leads to neural damage and dementia.